FNA biopsy of secondary nonlymphomatous malignancies in salivary glands: A multi‐institutional study of 184 cases. Issue 2 (21st December 2016) - Wang, He; Hoda, Raza S.; Faquin, William; Rossi, Esther Diana; Hotchandani, Nihar; Sun, Tianlin; Pusztaszeri, Marc; Bizzarro, Tommaso; Bongiovanni, Massimo; Patel, Viren; Jhala, Nirag; Fadda, Guido; et al.
Abstract : BACKGROUND: Secondary malignancies of salivary glands (SMSGs) are among the most common malignant neoplasms to involve the salivary glands. Fine‐needle aspiration biopsy (FNAB) of SMSG can present diagnostic challenges. The current report presents the largest such FNAB series to date. METHODS: A search of the pathology database from 6 academic institutions identified 184 FNAB cases of nonlymphomatous SMSG. RESULTS: Of the 184 cases, 171 were of the parotid glands, and 13 were of the submandibular glands; 130 patients were men, and 54 were women, and the mean patient age at diagnosis was 68 years. Metastatic squamous cell carcinoma (SCC) from all sites (n = 87) and melanoma (n = 67) constituted the majority of SMSGs. Less frequent SMSGs were comprised of metastatic carcinomas from distant organs (n = 16), including sites in the breast, lung, kidney, thyroid, pancreatobiliary, prostate, and bladder. Other uncommon SMSGs, including nasopharyngeal carcinoma (n = 3), sarcoma (n = 4), other metastatic skin‐derived carcinomas (n = 6), and metastatic chordoma (n = 1), also were observed. Ancillary tests were performed on 37 FNAB specimens (20.1%) to aid the evaluation. One hundred forty‐seven specimens (79.9%) had a definitive diagnosis with accurate tumor subtyping, 21 (11.4%) had a definitive malignant diagnosis but without specifying subtype, 9 (4.9%) had an indeterminate diagnosis, and 7 (3.8%) had a false‐negative diagnosis. CONCLUSIONS: SMSGs originate predominately from the head and neck and are more common in older men. Overall, the FNAB diagnosis of SMSG is accurate, but diagnostic challenges can be encountered, especially in SCC types of SMSG. Ancillary studies are needed for the definitive diagnosis of challenging cases. Cancer Cytopathol 2017;125:91–103. © 2016 American Cancer Society. Abstract : The fine‐needle aspiration biopsy diagnosis of secondary nonlymphomatous malignancy is accurate overall. However, diagnostic challenges can be encountered, especially in the squamous cell carcinoma type of secondary nonlymphomatous malignancy.